Strategi Solutif Kepala Sekolah Pada Pembelajaran Daring Selama Pandemi Covid 19 di SDN Sumput Sidoarjo - Triana Rosalina Noor (al-fikrah: Jurnal Manajemen Pendidikan, 2021)
This qualitative research is classified as a case study that aims to describe and analyze the principal's solution strategy for online learning during the Covid-19 pandemic at SDN SumputSidoarjo. The data were collected through observation, interviews with three people, namely the principal, secretary and treasurer of SDN SumputSidoarjo, and also documentary studies. Data analysis was carried out through the process of condensing data, presenting data and drawing conclusions. The results of this study showed that the Principal applied a solution strategy in the form of developing the potential of teachers through training for HR, providing online extracurricular services for students, preparing adequate learning tools for learning and optimizing the use of BOS(School Operational Funds). The obstacles faced in implementing the principal's strategies and solutions for learning during the Covid 19 pandemic were the human resource factors, heterogeneity of student guardians, limited funds and communication. In response to this, the Principal has taken a policy to develop HR competencies, relax financial financing and open a two-way communication forum between parents and schools.